Donald D. Walker papers - Walker, Donald D.
Correspondence, clippings, printed matter, and other papers concerning Frank Lloyd Wright, for whom Walker worked as a draftsman. Includes inscriptions and letters of recommendation from Wright and material relating to the U.S. stamp commemorating him. Correspondents include Edgar Tafel.
Architect.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Tafel, Edgar -- Correspondence; Wright, Frank Lloyd, -- 1867-1959.; Architects -- United States; Commemorative postage stamps -- United States; Architects